Roof collapse mechanisms for a shallow tunnel in two-layer rock strata incorporating the influence of groundwater. (April 2019) - Wang, H.T.; Wang, L.G.; Li, S.C.; Wang, Q.; Liu, P.; Li, X.J.
Abstract: It is inevitable that adverse conditions such as layered strata, groundwater, and ground overload will be encountered during the excavation of shallow tunnels. However, analytical theories on shallow tunnel stability are not well investigated while taking above factors into consideration together. In this paper, a shallow tunnel in two-layer rock strata is taken as an example. The influences of the groundwater table, ground overload, supporting force, etc., are considered. The corresponding kinematically admissible velocity fields for roof collapse under two cases are established. The analytical solutions of the curvilinear equations for failure of the roof surrounding rock masses and the critical burial depth of the shallow tunnel in Case I and Case II are obtained, respectively, based on upper bound theorem and variational principle. In addition, the influencing regularities of the roof collapse mechanisms under differing mechanical parameters are analyzed. It was found that the roof collapse range increases when the groundwater table drops or the supporting force, rock empirical parameter A, compressive strength, or tensile strength increase. Conversely, the roof collapse range decreases when the thickness of the upper stratum, pore water pressure coefficient, ground overload, rock empirical parameter B, or unit weight increase. The collapse range indicates the safety state of the tunnel roof. The larger the range is, the more external force power is required to generate collapse and the safer the roof is. Practically, it is efficient to improve the roof stability of the shallow tunnel by increasing the supporting force or employing the grouting technique to increase rock empirical parameter A and other strength parameters. Highlights: Two roof collapse mechanisms for a shallow tunnel in two-layer rock strata are proposed. The influences of groundwater, ground overload, supporting force, etc.,  are incorporated into the two mechanisms. The analytical solutions of roof collapse curves and critical burial depth for a shallow tunnel in two cases are derived. The proposed method is validated by comparison with the extant research. The influencing regularities of collapse mechanisms under differing parameters are obtained.